An integer programming model for the minimum interval graph completion problem - Lopes, Isabel Cristina (2015)
The minimum interval graph completion problem consists of, given a graph G = ( V, E ), ﬁnding a supergraph H = ( V, E ∪ F ) that is an interval graph, while adding the least number of edges |F| . We present an integer programming formulation for solving the minimum interval graph completion problem recurring to a characteri- zation of interval graphs that produces a linear ordering of the maximal cliques of the solution graph.